DEVELOPMENT OF THE BIG CASPIAN CONCEPT AND MODERN GEOPOLITICAL RELATIONS - K. A. Markelov (Современная наука и инновации, 2022)
The Caspian problem in the light of the natural resource and transport and communication potential, as well as the geopolitical significance of the region, is of particular relevance.